Abdominal Circumference, Blood Pressure, and Blood Sugar Rate in Adult Men - Asnaniar, Wa Ode Sri; Munir, Nur Wahyuni (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This research design was a quantitative study with a cross-sectional study design. The population in this study were adult males at the Faculty of Public Health, Universitas Muslim Indonesia. Samples were taken by total sampling method with a total of 33 samples. Data obtained through direct measurement of abdominal circumference, blood pressure and blood sugar levels. The data analysis used was the Pearson test correlative analysis to determine the correlation between abdominal circumference and blood pressure and blood sugar levels. The results showed a significant positive relationship between systolic blood pressure and abdominal circumference (r = 0.523; p = 0.002), while diastolic blood pressure had a negative and insignificant relationship (r = -0.038; p = 0.832). There was a positive and insignificant relationship between stomach circumference and blood sugar levels (r = 0.224; p = 0.211).